(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
Folklore constitutes a vital element of human cultural heritage, reflecting the collective memory, values, and social norms of communities. This paper explores the evolving role of folklore in scientific research, examining historical approaches, including the descriptive and historic-geographic methods, as well as functionalist perspectives that emphasize social cohesion and cultural continuity. The study further investigates contemporary conceptions of folklore, highlighting multidisciplinary frameworks that incorporate cognitive linguistics, structuralism, performance studies, and digital methodologies.